Online Gambling: A Comparative Analysis Under Civil and Syariah Law in Malaysia - Tuan Ibrahim, Tuan Muhammad Faris Hamzi; Nor Muhamad, Nasrul Hisyam; Baharuddin, Ahmad Syukran (Faculty of Law, Universitas Brawijaya, 2025)
The rapid development of digital technology and the widespread accessibility of the internet have transformed the gambling landscape in Malaysia. However, the legislation governing gambling under both civil and Syariah contexts was enacted during a pre-internet era, rendering it less effective and increasingly irrelevant in addressing contemporary challenges. Consequently, online gambling has emerged as a critical issue that is becoming increasingly difficult to regulate. This study aims to analyse the differing approaches of civil and Syariah law towards online gambling in Malaysia, as well as to identify the enforcement challenges faced by both legal systems. The methodology of this study adopts a qualitative doctrinal design through inductive and comparative approaches. Data were collected through document analysis of statutory provisions, court cases, and relevant literature. The findings of this study indicate that civil law tends to regulate gambling through licensing and stringent controls, permitting licensed gambling activities as provided under the Common Gaming Houses Act 1953 and the Lotteries Act 1952. However, civil law faces challenges in regulating online gambling, as the existing legal framework is primarily focused on physical gambling activities. This study argues for the reform of the Common Gaming Houses Act 1953 through an amendment to Section 2 (Interpretation), explicitly extending the meaning of “gaming” to include digital and online activities. In contrast, Syariah law absolutely prohibits gambling for Muslims, in accordance with Islamic teachings. Although nearly all states have enacted Syariah legislation prohibiting gambling, including online gambling, enforcement faces significant challenges such as technological limitations However, both legal systems play complementary roles in addressing online gambling: civil law regulates it through federal control, while Shariah law enforces its moral prohibition within Islamic jurisdiction. This study also recommends further research to enhance the legal framework governing online gambling, including leverage modern technologies to strengthen the enforcement of laws against online gambling in Malaysia.